Archaeobotanical study of Patagonian Holocene coprolites, indicators of diet, cultural practices and space use. (December 2016) - Martínez Tosto, Ana Cecilia; Burry, Lidia Susana; Arriaga, Mirta Olga; Civalero, María Teresa
Abstract: The analysis of coprolite inclusions is instrumental in exploring certain features of paleodiets and paleoenvironments, and in determining the time when the sites were occupied by those who deposited the feces. Plant remains found in palaeofeces can be recognized by means of optical microscopes and through microhistological techniques. The aim of this study is to perform a microhistological analysis of plant remains in probable human coprolites from the Cerro Casa de Piedra, Cueva 7 site, province of Santa Cruz, Argentina, with the purpose of identifying the plants included in the diet of the hunter - gatherers who lived in Patagonia during the Pleistocene - Holocene transition and the Holocene, of recognizing some of their cultural practices and of determining the seasonality of the shelters they used. Our microscope study of the samples revealed epidermal fragments of Ephedra sp. stem, leaf and fruit remains of Empetrum rubrum and Gaultheria mucronata, remains of vascular bundles of Azorella monantha leaves and of Armeria maritima epidermis. Only representatives of the Poaceae family were found among the monocots. Our microhistological study of coprolite provided evidence to endorse the consumption of fruits, namely of E . rubrum and G. mucronata. In addition, by determining the time of the year in which the mentioned species bear fruit, we were able to infer that humans used this cave in summer. Likewise, the identification of Ephedra sp., Armeria maritima and Azorella monantha also allowed us to infer that plants of these species were used as medicine and fuel. Highlights: Microhistological techniques reveal plant remains in paleofeces. Coprolite analyses provide information on prehistoric diet. Paleodiet analysis reveals the seasonality in which the site was occupied.